Inhibition of Streptococcus mutans biofilm accumulation and development of dental caries in vivo by 7-epiclusianone and fluoride - Murata, Ramiro M.; Branco-de-Almeida, Luciana S.; Franco, Eliane M.; Yatsuda, Regiane; Santos, Marcelo H. dos; Alencar, Severino M. de [UNESP]; Koo, Hyun; Rosalen, Pedro L. (Taylor & Francis Ltd, 2010)
7-Epiclusianone (7-epi), a novel naturally occurring compound isolated from Rheedia brasiliensis, effectively inhibits the synthesis of exopolymers and biofilm formation by Streptococcus mutans. In the present study, the ability of 7-epi, alone or in combination with fluoride (F), to disrupt biofilm development and pathogenicity of S. mutans in vivo was examined using a rodent model of dental caries. Treatment (twice-daily, 60s exposure) with 7-epi, alone or in combination with 125 ppm F, resulted in biofilms with less biomass and fewer insoluble glucans than did those treated with vehicle-control, and they also displayed significant cariostatic effects in vivo (p < 0.05). The combination 7-epi + 125 ppm F was as effective as 250 ppm F (positive-control) in reducing the development of both smooth-and sulcal-caries. No histopathological alterations were observed in the animals after the experimental period. The data show that 7-epiclusianone is a novel and effective antibiofilm/anticaries agent, which may enhance the cariostatic properties of fluoride.
Keywords: benzophenone; Streptococcus mutans; dental caries; biofilms; fluoride; extracellular polysaccharides